Death and mastery : psychoanalytic drive theory and the subject of late capitalism - Fong, Benjamin Y. (New directions in critical theory., 2016)
The first philosophers of the Frankfurt School famously turned to the psychoanalytic theories of Sigmund Freud to supplement their Marxist analyses of ideological subjectification. Since the collapse of their proposed "marriage of Marx and Freud," psychology and social theory have grown increasingly apart to the impoverishment of both. Returning to this unholy union, Benjamin Y. Fong reconstructs the psychoanalytic "foundation stone" of critical theory in the effort to once again think together the possibility of psychic and social transformation. Drawing on the work of Hans Loewald and Jacque.